Evaluating gifted students’ perceptions of the characteristics of their effective teachers - Aboud, Yusra Zaki (Frontiers in Education, 2023)
Due to the special needs of gifted students, it is crucial that their teachers are carefully selected in order to give gifted students the greatest educational experience. The study involved 120 teachers from Saudi Arabia, Bahrain, and the United Arab Emirates along with 300 gifted students, both males (n = 144) and females (n = 156). Teachers of gifted students involved in the study were asked to complete the Preferred Teacher Characteristics Scale (PICS); additionally, teachers filled out a background questionnaire. While gifted students responded to three open-ended questions, The findings corroborated the idea that gifted students perform better in an environment where their teachers’ personalities are evident. This finding was in line with the preferences of teachers as measured by the PCIS scale, which revealed that students tended to value teachers more for their personal characteristics than for their professional ones. Many personal characteristics were highly regarded by the gifted students, who in this study believed they contributed to a teacher’s effectiveness. Personal integrity, tolerance, tenderness, friendliness, a sense of humor, and an openness to new experiences were among these characteristics.